(untitled) (AYUSHDHARA, 2024)
Chronic kidney disease (CKD) encompasses a spectrum of pathophysiologic processes associated with abnormal kidney function, often with a progressive decline in glomerular filtration rate. In Ayurveda, CKD is addressed under the concept of Mutravah Srotas Vikar, and also Mutrakshaya will be seen. The originators of Ayurveda, Charaka, Sushruta, and Vagbhatta, were aware about common illnesses. This illness affects all three Doshas and all Dushyas. Microangiopathy is caused by microvessel blockage, which is the responsibility of Kapha and the kidney’s structural deterioration is caused by Vata. It is often left unnoticed at the early stages and generally diagnosed at later stages as the patient remains asymptomatic for long time. The purpose of this study was to find out an effective and well accepted drug with minimal or no complications for this illness. 30 patients who were diagnosed with Mutradoshvikara w.s.r. to Chronic Kidney Disease were allocated randomly into two groups. The trial drug i.e., Trinpanchmoola Kashaya 50ml twice a day was given to 15 patients of Group I and trial drug i.e., Punarnava Kashaya 50ml twice a day was given to 15 patients of Group II for the duration of 3 months. Subjective and objective parameters were assessed before and after the completion of trial. Data obtained during the trial was tabulated and statistically analysed.